Electron Microscopic Observations on the Structure of the Envelopes of Mature Elementary Bodies and Developmental Reticulate Forms of Chlamydia psittaci - Tamura, A. (1971)
Purified suspensions of Chlamydia psittaci were prepared from L cells. Thin sections of intact elementary bodies and intact developmental reticulate bodies and of their purified envelopes were observed by electron microscopy. In both intact organisms and partially purified envelopes, two membranous structures, each appearing in electron micrographs as two darkly stained layers, were observed. In the elementary body sections, the outer membrane was round, apparently rigid, and was not soluble in 0.5% sodium dodecyl sulfate. The inner layer was irregular in shape and was completely removed by detergent treatment. We interpret these results to indicate that the outer rigid layer of the envelope is the cell wall and the inner layer is the cytoplasmic membrane. When the fragile reticulate body envelopes were similarly studied, the outer cell wall was clearly visible, and some evidence of an inner membrane was seen. After treatment with nucleases and detergent, all evidence of inner or cytoplasmic membrane was removed, but the outer cell wall remained. Thus, it appears that the cell wall of this organism is continuous throughout the growth cycle and that the fragility and lack of rigidity of the reticulate body cell is due to changes in chemical composition or structure of the cell wall.